2017
DOI: 10.1186/s40623-017-0733-0
|View full text |Cite
|
Sign up to set email alerts
|

3-D dynamic rupture simulations of the 2016 Kumamoto, Japan, earthquake

Abstract: Using 3-D dynamic rupture simulations, we investigated the 2016 M w 7.1 Kumamoto, Japan, earthquake to elucidate why and how the rupture of the main shock propagated successfully, assuming a complicated fault geometry estimated on the basis of the distributions of the aftershocks. The M w 7.1 main shock occurred along the Futagawa and Hinagu faults. Within 28 h before the main shock, three M6-class foreshocks occurred. Their hypocenters were located along the Hinagu and Futagawa faults, and their focal mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…In this study, we focused on an M 5 earthquake sequence that occurred on a single fault plane. Fault structures inside the plate, however, are usually more complex, and their interactions play important roles in the 3‐D release of intraplate stress (Urata et al, 2017). When faults are randomly distributed in space, shear strain energy density can be a measure of the average shear stress over the faults (Saito et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we focused on an M 5 earthquake sequence that occurred on a single fault plane. Fault structures inside the plate, however, are usually more complex, and their interactions play important roles in the 3‐D release of intraplate stress (Urata et al, 2017). When faults are randomly distributed in space, shear strain energy density can be a measure of the average shear stress over the faults (Saito et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…One is based on the observation of stress rotation due to the earthquake, which suggested that the maximum shear stress is smaller than 10 MPa (Yoshida et al, ). Another is proposed from the dynamic rupture simulations reproducing the foreshock and main shock, indicating that the maximum shear stress should range from 15 to 30 MPa (Urata et al, ). Our estimation of the lower limit of maximum shear stress supports the latter background stress state and dismisses the extraordinarily low magnitude of stress in the former model.…”
Section: Discussionmentioning
confidence: 99%
“…The Kumamoto earthquake sequence began with a M w 6.2 event at 21:26 JST (UTC + 9) on 14 April 2016, and the M w 7.0 mainshock occurred at 01:25 JST on 16 April 2016 (e.g., Urata et al, 2017). We refer to these two events hereafter as the "largest foreshock" and "mainshock," respectively.…”
Section: Datamentioning
confidence: 99%